(untitled) (Al-Academy, 2023)
Museum education is of great importance to an appropriate representation of museums’ collections and exhibits, including traditional fashion. Therefore, museum educators/curators need to be equipped with the most essential skills in their profession in order to adequately present the museum’s history and holdings. This could be achieved through specialized training programs. However, Arab countries are still behind in terms of museum education. Therefore, this article aims to shed light on this issue by assessing the knowledge and skills possessed by museum educators/curators and how training programs could affect them